‘Looking out fo r the Horizon The music of Gustav Mahler in the light of the theory of the aesthetic of reception by Hans Robert Jauss - Mika, Bogumiła (Interdisciplinary Studies in Musicology, 2018)
The theory of the aesthetic of reception proposed by Jauss in the field of literature can be applied to research into the reception of the music of Gustav Mahler. In creating his symphonies ‘with every means of accessible technique’, the composer achieved what might be described as a reinterpretation of the conception of selected genres. In this way he disturbed the traditional ‘horizon of expectations’ of the potential audience, and significantly distanced himself from it. The most important consequence of this was the lack of understanding of his music by a section of his contemporary audience. Mahler justified the rightness of his own creative intuition with the famous sentence ‘my time will come’. In her article the author presents the fundamental theses of Jauss’s aesthetic of reception relating to his understanding of the ‘horizon of expectations’. She also indicates the manner in which Mahler distanced himself from that ‘horizon’, and how in individual symphonies he contributed to the expansion and reinterpretation of conceptions of genres which had previously been based on knowledge shared by the composer and the listener.